Brain activity and connectivity in response to negative affective stimuli: Impact of dysphoric mood and sex across diagnoses. Issue 11 (6th October 2016) - Mareckova, Klara; Holsen, Laura M.; Admon, Roee; Makris, Nikos; Seidman, Larry; Buka, Stephen; Whitfield‐Gabrieli, Susan; Goldstein, Jill M.
Abstract: Negative affective stimuli elicit behavioral and neural responses which vary on a continuum from adaptive to maladaptive, yet are typically investigated in a dichotomous manner (healthy controls vs. psychiatric diagnoses). This practice may limit our ability to fully capture variance from acute responses to negative affective stimuli to psychopathology at the extreme end. To address this, we conducted a functional magnetic resonance imaging study to examine the neural responses to negative valence/high arousal and neutral valence/low arousal images as a function of dysphoric mood and sex across individuals ( n = 99) who represented traditional categories of healthy controls, major depressive disorder, bipolar psychosis, and schizophrenia. Observation of negative (vs. neutral) stimuli elicited blood oxygen‐level dependent responses in the following circuitry: periaqueductal gray, hypothalamus (HYPO), amygdala (AMYG), hippocampus (HIPP), orbitofrontal cortex (OFC), medial prefrontal cortex (mPFC), and greater connectivity between AMYG and mPFC. Across all subjects, severity of dysphoric mood was associated with hyperactivity of HYPO, and, among females, right (R) AMYG. Females also demonstrated inverse relationships between severity of dysphoric mood and connectivity between HYPO ‐ R OFC, R AMYG ‐ R OFC, and R AMYG ‐ R HIPP. Overall, our findings demonstrated sex‐dependent deficits in response to negative affective stimuli increasing as a function of dysphoric mood state. Females demonstrated greater inability to regulate arousal as mood became more dysphoric. These findings contribute to elucidating biosignatures associated with response to negative stimuli across disorders and suggest the importance of a sex‐dependent lens in determining these biosignatures. Hum Brain Mapp 37:3733–3744, 2016 . ©2016 Wiley Periodicals, Inc .